Comparison of pulse oximetry and earlobe blood gas with CO-oximetry in children with sickle cell disease: a retrospective review. Issue 1 (15th June 2020) - Arigliani, Michele; Zheng, Sean; Ruiz, Gary; Chakravorty, Subarna; Bossley, Cara J; Rees, David; Gupta, Atul
Abstract : Objectives: To investigate the agreement between pulse oximetry (SpO2 ) and oxygen saturation (SaO2 ) measured by CO-oximetry on arterialised earlobe blood gas (EBG) in children and adolescents with sickle cell disease (SCD). Design and setting: We retrospectively reviewed 39 simultaneous and paired SaO2 EBG and SpO2 measurements from 33 ambulatory patients with SCD (32 subjects with Haemoglobin SS and one with Haemoglobin Sß +, 52% male, mean±SD age 11.0±3.6, age range 5–18). Measurements were performed between 2012 and 2015 when participants were asymptomatic. Hypoxaemia was defined as SaO2 ≤93%. A Bland-Altman analysis was performed to assess the accuracy of SpO2 as compared with EBG SaO2 . Results: The mean±SD SpO2 and SaO2 values in the same patients were, respectively, 93.6%±3.7% and 94.3%±2.9%. The bias SpO2 –SaO2 was −0.7% (95% limits of agreement from −5.4% to 4.1%) and precision was 2.5%. In 9/39 (23%) cases, the difference in SpO2 –SaO2 was greater than the expected error range ±2%, with SaO2 more often underestimated by SpO2 (6/9), especially at SpO2 values ≤93%. Thirteen participants (33%) were hypoxaemic. The sensitivity of SpO2 for hypoxaemia was 100%, specificity 85% and positive predictive value 76%. Conclusions: Pulse oximetry was inaccurate in almost a quarter of measurements in ambulatory paediatric patients with SCD, especially at SpO2 values ≤93%. In these cases, oxygen saturation can be confirmed through EBG CO-oximetry, which is easier to perform and less painful than traditional arterial blood sampling.